Trends in the Use of CBT to Reduce Anxiety in Bipolar Patients at Islamic Hospitals - Jamilah, Noor (Institut Agama Islam Negeri Parepare, 2024)
This study aims to evaluate the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing anxiety symptoms and improving mood stability in patients with bipolar disorder at an Islamic hospital. The research employs an experimental method with a randomized controlled trial (RCT) design, dividing participants into two groups: one receiving individual CBT and the other participating in group CBT. Data were collected from patients diagnosed with bipolar disorder and comorbid anxiety, using surveys, structured interviews, and psychometric tools such as the Beck Anxiety Inventory (BAI) and Young Mania Rating Scale (YMRS). The results show that CBT significantly reduced average anxiety scores by 48% after 12 therapy sessions, both in individual and group formats. Social support in group therapy enhanced the effectiveness of CBT in reducing anxiety and improving mood stability. Additionally, the duration of therapy influenced outcomes, with participants undergoing more than 12 sessions showing more stable results. However, challenges in adherence to CBT tasks outside of therapy sessions were noted, indicating the need for a more flexible approach to increase patient engagement. The study concludes that CBT is an effective intervention in the context of an Islamic hospital for patients with bipolar disorder and anxiety.